Application of Improved Multi-objective Differential Evolution Algorithm in the Optimal Operation of Reservoirs - SUN Qiurong; LI Yong; TANG Qian; WU Shaofei (Renmin Zhujiang)
The multi-objective optimal operation of reservoirs is a complex system optimization,and it belongs to the scope of high-dimension,multi-constraint,and nonlinear optimization.The intelligent optimization algorithm has the shortcomings of less non-inferior solutions,uneven distribution and non-convergence when solving the multi-objective optimal operation of reservoirs.Based on the above problems,this paper proposes a new idea to improve the multi-objective differential evolution algorithm by adding the elite retention mechanism and maintaining the external elite set with the crowding distance,establishes the multi-objective optimal operation model for reservoirs,and applies it for realizing the multi-objective optimal operation of Zhanghe Reservoir.The results show that the algorithm can obtain non-inferior solution set with uniform distribution,which proves that it is effective in multi-objective optimal operation of reservoirs.